2011
DOI: 10.1108/00483481111106075
|View full text |Cite
|
Sign up to set email alerts
|

The role of organisational commitment in the analysis of resistance to change

Abstract: 2013),"The limitations of dispositional resistance in relation to organizational change", Management Decision, Vol. 51 Iss 4 pp. 761-780 http:// dx., (2003),"Resistance to change: a literature review and empirical study", Management Decision, Vol. 41 Iss 2 pp. 148-155 http:// dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Plea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
2
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 57 publications
5
47
2
11
Order By: Relevance
“…While the idea of organizational change seems straight-forward, the reality is that the majority of organizational change initiatives fail or are not sustained (Beer & Nohria 2000). While there are several schools of thought when it comes to the failure of change initiatives, there is strong support for the view that employee resistance to change is a primary contributor (Elias 2009;Peccei, Giangreco, & Sebastiano 2011). For example, a positive attitude toward change is likely to see an employee actively engaged in the change process, and assisting in the realisation of the goals associated with the change initiative.…”
Section: The Importance Of Workplace Relationships and Attitudes Towamentioning
confidence: 99%
“…While the idea of organizational change seems straight-forward, the reality is that the majority of organizational change initiatives fail or are not sustained (Beer & Nohria 2000). While there are several schools of thought when it comes to the failure of change initiatives, there is strong support for the view that employee resistance to change is a primary contributor (Elias 2009;Peccei, Giangreco, & Sebastiano 2011). For example, a positive attitude toward change is likely to see an employee actively engaged in the change process, and assisting in the realisation of the goals associated with the change initiative.…”
Section: The Importance Of Workplace Relationships and Attitudes Towamentioning
confidence: 99%
“…The SFI factor included questions related to providing adequate resources, time, and funding to pursue Similarly, Oreg (2006) studied employees experiencing a merger in the defense industry, and found that information sharing was positively linked to trust in management. A study of middle management in an Italian national electricity company showed that involvement in change predicted attitudes toward change (Peccei, Giangreco, & Sebastiano, 2011). Qian and Daniels (2008) Taken in the aggregate, the findings of this study in terms of procedural justice support the conceptualization of this variable as an important condition that shapes respondent views and, most likely, impacts engagement in other productive behaviors that promote organizational effectiveness (Folger, Crapanzano, Timmerman, Howes, & Michell, 1996;Konovsky, 2000;O'Reilly & Chatman, 1986) Conflict Conflict may be an anticipated outcome of adopting innovation or a work context variable.…”
Section: Justicesupporting
confidence: 64%
“…As such, little research has been done along these lines. Studies have found that change projects tend to influence the degree to which employees identify with their organizations [83,84].…”
Section: Discussionmentioning
confidence: 99%